ANALYSE THE DEVELOPMENT OF FOREIGN TRADE PERFORMANCE AND INDICATORS IN THE IRAQI ECONOMY USING THE GRAVITY MODEL - Mostafa Kazemi Najaf Abadi, Hussein Abbas Hassan Al-Zubaidi, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to measure the determinants of foreign trade in Iraq using the Gravity Model and the adoption of data of Iraq with the most important trading partners for the period 2003-2018.It relies on the descriptive analytical approach, in studying the model of gravity of foreign trade in theory, then examining the reality and development of foreign trade in Iraq and its indicators. The study showed that Iraq is largely open to foreign trade, which represents approximately 80% of the country's gross domestic product. The new trade policy of the Iraqi government aims to integrate the country's economy into regional and international markets, and therefore the country has very few trade barriers. Crude oil represents 90% of Iraqi exports, while the remaining from petroleum products. The rate of exports of output recorded a decline, from 7.69% in 1990 to 43.97%, and yet it is still far in the last decade. Its importance to the economy is increasing as it is the first source of output. The study also found that Iraq exports five products with a comparative advantage.